Drug-Induced Liver Disturbance During the Treatment of COVID-19 - Zhai, Guanghua; Li, Meifen; Wang, Ying; Wu, Jian (Frontiers in Pharmacology, 2021)
An outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) occurred in Wuhan, China, at the end of 2019. The World Health Organization named the resulting infectious disease as coronavirus disease-2019 (COVID-19). Many studies concluded that patients infected with SARS-CoV-2 have different degrees of liver disturbance. However, the relationship between the drugs used for COVID-19 treatment and liver disturbance remains controversial. It is essential to evaluate the potential liver damage caused by various drugs in order to help guide clinical practice. This review analyzed the effect of drugs on hepatic function during the treatment of COVID-19.